Ethnofuturism and Place-Making: Bengt Pohjanen’s Construction of Meänmaa - Heith, Anne (Journal of Northern Studies, 2018)
The article examines the Tornedalian author Bengt Pohjanen’s construction of Meänmaa [literally ‘Our land’] through an analysis of a selection of texts in which the concept “Meänmaa” is used. Meänmaa refers to the border area between Sweden and Finland in the Torne Valley. The making of Meänmaa is related to ethnofuturism, an aesthetic program launched in Estonia in the 1980s. Its aim is to strengthen threatened Uralic cultures and languages. The conclusion presented is that ethnofuturism provides a framework for present-day identityformation and the making of a specific place called Meänmaa against the backdrop of a history of assimilationist policies and marginalisation.